Autoradiographic and electron microscopic study of embryonic nutrition in the teleost, clinus superciliosus - Veith, Walter Julius (Department of Biological Sciences, 2023)
It was established that C. superciliosus is a viviparous teleost. Moreover, breeding occurs throughout the year and the species is characterized by a high incidence of superembryonation, with as many as twelve broods of differing ages developing simultaneously. Autoradiographic studies revealed that the embryo absorbed nutrients through the epidermis initially, but with an increase in embryo-size, there is a shift from epidermal to intestinal absorption of nutrients. Scanning electron microscopy revealed that the epidermal surf ace area is enlarged by the essence of macroridges, which in turn have microvilli and microridges on their free surfaces. The highest incidence of macroridges occurs in the expanded yolk sac and pericardial s ac re ions and the epidermal surface area is at its greatest in embryos 6,8mm long. Thereafter the macroridges gradually disappear and the embryonic surface area is reduced.